148 Senticol III: international validation study of sentinel node biopsy in early cervical cancer. A gineco, engot and gcig study. (18th September 2019) - Lecuru, F; Mc Comack, M; Hillemans, P; Anota, A; Leitao, M; Sweemer, R; Fujiwara, K; Mathevet, P; Zanagnolo, V; Raza Mirza, M; Ferron, G; Plante, M; et al.
Abstract : Objectives: The aim of the present study is to demonstrate a similar survival and a better quality of life when compared to PLN. Methods: SENTICOL III is an international prospective multicenter randomized trial. The primary objective is a « co-primary » objective associating Disease Free Survival (DFS) and Health Related Quality of Life. The hypothesis is that SLN biopsy alone provides similar DFS and better quality of life. Outcome of patients with ITC and micrometastases will belong to secondary objectives (with overall survival, recurrence free survival, cost analysis, etc.). Patients with squamous or adenocarcinoma from FIGO 2018 stage Ia1 with lymphovascular invasion to Ib2 and IIa1, will be included. SLN mapping will use isotopic detection ± blue dye or ICG. Frozen section of SLN will be done in case of "optimal" mapping. Patients with negative SLN will be randomized intraoperatively 1:1 to SLN only or SLN + PLN. A quality assurance program will ensure surgical competency and a standardized pathological evaluation. 950 patients have to be included in 3 years, with 4 years of follow-up. (3 years-disease free survival of 85%, with a non-inferiority margin of 5% (80 vs 85%, HR = 1.373), a unilateral alpha error of 5%, and a power of 80%). Results: Inclusions are open in France, and an international collaboration has been developed through GCIG and ENGOT. (NCT03386734 ). CHU Besançon is the sponsor for France Conclusions: A validation study is needed for early cervical cancer. SENTICOL III will answer the question of the deescalation for nodal staging.